2019
DOI: 10.18805/ijar.b-1003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of monensin, yeast and glucogenic precursor on growth performance, ruminal fermentation and digestive kinetics of feedlot steers

Abstract: The objective of this study was to evaluate the effect of supplementation of monensin, yeast and glucogenic precursors on growth performance and digestive characteristics of feedlot beef cattle. The treatments evaluated were: control, monensin (40 mg/kg DM), S. cerevisiae (10 g/a/d) and a mix of 1,2-propanediol and calcium propionate as glucogenic precursors (20 g/a/d) as D1, D2, D3 and D4, respectively. In trial 1, eighty steers (261±8 kg) were evaluated for 120d for growth performance variables. Thus, supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…When CaPr is supplemented alone, it undergoes hydrolysis within the acidic pH of the rumen, resulting in the formation of Ca 2+ and propionic acid [7]. This process yields several effects at the rumen level, including (1) alteration of the volatile fatty acid (VFA) pattern [5]; (2) reduction in methane production; (3) improved digestibility of the DM; (4) enhanced fermentation efficiency [4]; and (5) improved responsiveness of insulin in glucose metabolism [6], which plays a role in both fat deposition and muscle growth. As a cumulative outcome of these mechanisms, there is a promotion of energy status achieved through the heightened synthesis of glucose via gluconeogenesis [7].…”
Section: Productive Performancementioning
confidence: 99%
See 1 more Smart Citation
“…When CaPr is supplemented alone, it undergoes hydrolysis within the acidic pH of the rumen, resulting in the formation of Ca 2+ and propionic acid [7]. This process yields several effects at the rumen level, including (1) alteration of the volatile fatty acid (VFA) pattern [5]; (2) reduction in methane production; (3) improved digestibility of the DM; (4) enhanced fermentation efficiency [4]; and (5) improved responsiveness of insulin in glucose metabolism [6], which plays a role in both fat deposition and muscle growth. As a cumulative outcome of these mechanisms, there is a promotion of energy status achieved through the heightened synthesis of glucose via gluconeogenesis [7].…”
Section: Productive Performancementioning
confidence: 99%
“…It has been observed that the gluconeogenic precursor calcium propionate (CaPr) alters energy metabolism in two ways when supplemented in ruminant diets: firstly, by altering rumen fermentation through improvements in ruminal dry matter (DM) digestibility, thereby increasing the proportion of ruminal propionate, and decreasing methane production [4,5]. Another way is by improving insulin's action on glucose metabolism [6], thereby promoting an increase in energy status through enhanced glucose synthesis via gluconeogenesis in the liver [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that gluconeogenic precursor calcium propionate (CaPr) alters energy metabolism when supplemented in ruminant diets. Specifically, it has two significant effects: (1) It alters rumen fermentation by improving ruminal DM digestibility, increasing the proportion of ruminal propionate, and reducing methane production [18,19], and (2) it enhances the action of insulin on glucose (GLU) metabolism [20], promoting an increase in energy status through enhanced GLU synthesis via gluconeogenesis in the liver [21]. In this context, Carrillo-Muro et al [22,23], studying finishing diets for lambs, found that 10 g of CaPr/lamb/d for 28 d increased dry matter intake (DMI) by 1 to 13%, ADG by 28%, ADG/DMI ratio by 17 to 25%, and BW by 5 to 7%.…”
Section: Introductionmentioning
confidence: 99%